Progress in Research on the Involvement of Intestinal Flora in Depression Based on the “Microbial-Gut-Brain” Axis - XU Jinzhao, MA Yanshi, WANG Danping, ZHANG Xuyan, YANG Xiaoying, YU Yansong, MA Longkai, TANG Mengqi, XU Xiaoxi (Shipin Kexue, 2023)
Depression is one of the most common mental disorders in modern society. The disease not only seriously harms people’s quality of life, but also brings a huge burden to families and society because of the high suicide rate and disability rate caused by it. Recent studies have shown that the intestinal flora plays an important role the occurrence and progression of depression and dysfunctional gut-brain communication may be an essential pathological mechanism of depression. The “microbiota-gut-brain” (MGB) axis allows the intestinal flora to participate in the two-way information exchange between the intestine and the brain. Most previous studies mainly focus on exploring the individual characteristics of the intestinal flora in patients with depression and the relationship between the intestinal flora and the occurrence of depression, revealing that maintaining a healthy intestinal flora may be a new idea for the prevention and treatment of depression in the future. This article summarizes recent progress in this research field. We hope that this review can provide insights into the action mechanism of anti-depressive agents from the perspective of the MGB axis, and also provide a reference for the application of probiotics in new depression treatments.